Modeling and Parameter Estimation in Biofuel Discontinuous Production by Hydrogen Forming Bacteria (HFB) - Paulo, Cecilia Inés (2013)
In this work, we study the hydrogen production through a dark fermentation process by hydrogen forming bacteria consortium. In this sense, fermentation experiments are performed in a discontinuous reactor using glucose as the carbon source. Product and substrate profiles are measured in order to study the production of bio hydrogen. A kinetic model for the batch bioreactor that describes the production of all fermentation products, the growth of biomass and the consumption of substrates is developed. The model comprises fifteen differential equations and one algebraic equation. We formulate a parameter estimation problem for the bioreactor model. Fifteen input parameters are estimated taking account the experimental data obtained in the present work. The maximum hydrogen yield obtained was 2.68 mol H2/mol glucose and the highest hydrogen production rate observed was 1.61 l H2/ l-day. Numerical results show good agreement between experimental data and simulated profiles.